1970
DOI: 10.1172/jci106269
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of renal bicarbonate reabsorption by extracellular volume

Abstract: AB STR A CT The ability of the kidney to reabsorb bicarbonate is held to be a function of plasma C02 tension, carbonic anhydrase activity, and potassium stores. The effects of alterations of extracellular volume on bicarbonate reabsorption were studied in dogs whose arterial Pco2 was kept constant at 40 mm Hg (range 35-45 mm Hg).The effect of extracellular volume expansion was studied in dogs receiving hypertonic bicarbonate and isotonic saline, isotonic saline alone (two of the animals in this group received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
3

Year Published

1972
1972
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(62 citation statements)
references
References 15 publications
(14 reference statements)
5
54
0
3
Order By: Relevance
“…Clearance studies in dogs, rats, and man have all demonstrated that ECF volume expansion inhibits fractional bicarbonate reabsorption (3)(4)(5)(6)8). A prevalent view has been that this inhibition occurs in the proximal tubule and is related to increased bicarbonate back leak (20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearance studies in dogs, rats, and man have all demonstrated that ECF volume expansion inhibits fractional bicarbonate reabsorption (3)(4)(5)(6)8). A prevalent view has been that this inhibition occurs in the proximal tubule and is related to increased bicarbonate back leak (20).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous clearance studies have examined the effect of acutely increasing plasma bicarbonate concentration on bicarbonate absorption (1,(3)(4)(5) (9). The In previous studies, the rate of proton secretion was examined as a function of luminal bicarbonate concentration (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But still other possible mechanisms may be involved, as previously mentioned (25). Enforced activity of cellular Na ϩ /H ϩ exchangers (18,36) as well as Na ϩ /H ϩ ion exchanges on the extracellular glycosaminoglycans (19) and/or a Na-induced expansion of extracellular volume, resulting in a decrease in HCO 3 Ϫ reabsorption (3,38,52,58), can contribute to mediation of the effect of NaCl on acid-base balance. Summarizing, with high NaCl intake, renal loss of bicarbonate but also excess acid production could be reasonably expected to affect acid-base status.…”
Section: Discussionmentioning
confidence: 98%
“…El mecanismo de accion no estd bien claro y probablemente este relacionado con el efecto clo~ ruretico y de contraction del espacio extracelular (22) que mejora la absorcion proximal de bicarbonato. Ademas es bien conocido el efecto de la hidroclorotiazida que dismimiye la excretion de calcio urinario.…”
Section: Radiografidsunclassified